Pusa Mangal (HI 8713) A durum wheat variety boosting economy and nutritional security of central zone wheat farmers - Ambati, Divya; Prasad, S V Sai; Singh, Jang B; Phuke, Rahul M; Singh, A K; Sharma, K C; Upendra, S (Indian Farming, 2022)
Durum wheat cultivation is found to be highly profitable in central India due to varieties having high yield potential, rust resistance and high tolerance to drought and heat, which ensure more production with less irrigation. Around 13% of increase in durum wheat area was found in Madhya Pradesh compared to the durum wheat area in the last 5 years. With the rising demand from milling industries in and around Madhya Pradesh, farmers are increasingly taking up the cultivation of durum wheat. HI 8713 is a durum wheat variety with high yield, wider adaptability, high yellow pigment (7.16 ppm), good levels of essential micronutrients, and excellent dual quality grain with high levels of resistance to stem and leaf rust. Quality traits, viz. high hectolitre weight, less gruel solid loss and good grain appearance make Pusa Mangal, a best choice for good quality pasta. The success stories of farmers growing HI 8713 in terms of net revenue, cost benefit ratio and demand for the seed ensure Pusa Mangal can offer economic and nutritional security for wheat farmers of Central zone.